The advertising handbook - Brierley, Sean , 1966-; Powell, Helen (Media practice, 2009)
This book unravels the how & why of advertising and places the industry in its social, historical & political context. Focusing on key debates, it explores the competitive practices & discourses which govern the industry & those who work in it.